The immediate effects of foot orthosis geometry on lower limb muscle activity and foot biomechanics - Reeves, J.; Jones, R.; Liu, A.; Bent, L.; Nester, C. (Journal of Biomechanics, 2021)
Foot orthoses (FOs) are used to treat clinical conditions by altering the external forces applied to the foot and thereafter the forces of muscles and tendons. However, whether specific geometric design features of FOs affect muscle activation is unknown. The aim of this study was to investigate if medial heel wedging and increased medial arch height have different effects on the electromyography (EMG) amplitude of tibialis posterior, other muscles of the lower limb and the kinematics and kinetics at the rearfoot and ankle. Healthy participants (n = 19) walked in standardised shoes with i) a flat inlay; ii) a standard shape FOs, iii) standard FOs adjusted to incorporate a 6 mm increase in arch height, iv) and standard FOs adjusted to incorporate an 8° medial heel wedging and v) both the 6 mm increase in arch height and 8° increase in medial wedging. EMG was recorded from medial gastrocnemius, peroneus longus, tibialis anterior and in-dwelling tibialis posterior muscles. Motion and ground reaction force data were collected concurrently. Tibialis posterior EMG amplitude reduced in early stance with all FOs (Etap2 = 0.23-1.16). Tibialis posterior EMG amplitude and external ankle eversion moment significantly reduced with FOs incorporating medial wedging. The concurrent reduction in external eversion moment and peak TP EMG amplitude in early stance with medial heel wedging demonstrates the potential for this specific FOs geometric feature to alter TP activation. Medial wedged FOs could facilitate tendon healing in tibialis posterior tendon dysfunction by reducing force going through the TP muscle tendon unit.